2019
DOI: 10.1038/s41418-019-0409-3
|View full text |Cite|
|
Sign up to set email alerts
|

Impaired adult neurogenesis is an early event in Alzheimer’s disease neurodegeneration, mediated by intracellular Aβ oligomers

Abstract: Alterations of adult neurogenesis have been reported in several Alzheimer's disease (AD) animal models and human brains, while defects in this process at presymptomatic/early stages of AD have not been explored yet. To address this, we investigated potential neurogenesis defects in Tg2576 transgenic mice at 1.5 months of age, a prodromal asymptomatic age in terms of Aβ accumulation and neurodegeneration. We observe that Tg2576 resident and SVZ-derived adult neural stem cells (aNSCs) proliferate significantly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 49 publications
6
78
3
2
Order By: Relevance
“…Of particular relevance here is that adult neurogenesis is linked to AD [149,150], and impaired adult neurogenesis could be an early event in AD [151]. Conceivably, neuronal vulnerability to AD etiology may be exacerbated by earlier defects in the progenitor cells, while adult neurogenesis could be a compensatory response to neuronal loss to the disease condition.…”
Section: Effect On Adult Neurogenesismentioning
confidence: 96%
“…Of particular relevance here is that adult neurogenesis is linked to AD [149,150], and impaired adult neurogenesis could be an early event in AD [151]. Conceivably, neuronal vulnerability to AD etiology may be exacerbated by earlier defects in the progenitor cells, while adult neurogenesis could be a compensatory response to neuronal loss to the disease condition.…”
Section: Effect On Adult Neurogenesismentioning
confidence: 96%
“…Numerous studies have demonstrated the neuroprotective effects of nutraceuticals against toxic compounds associated with neurodegenerative diseases, via mechanisms such as modulation of energy metabolism, oxidative stress, neuroin ammation as well as promotion of neurogenesis via growth factors and neurotrophins [22,23]. In particular, the relationship between adult neurogenesis and AD has been debated in recent years [24,25]. Previous studies have reported that the reduction of expression of neurogenesis markers in the SVZ and DG regions of post-mortem AD brain.…”
Section: Discussionmentioning
confidence: 99%
“…Other APP metabolites, such as sAPP-α, sAPP-β, Aβ peptides, and APP intracellular C-terminal domain (AICD) appear to modulate various functions in NSCs, including proliferation, neurogenesis, gliogenesis, or cell death [139]. Scopa, et al [140] reported neurogenesis defects in a prodromal asymptomatic age (1.5 months of age) of TG2576 transgenic mice, in which the proliferation of NSCs was significantly reduced and the NSCs failed to differentiate into mature neurons. This reduction depended on the formation and accumulation of intracellular Aβ oligomers in NSCs, indicating the negative impact of Aβ oligomers on neurogenesis.…”
Section: Known Modulators Of Adult Neurogenesis and The Effects Of Admentioning
confidence: 99%